Geospatial analysis on open space effectiveness as a social place - Hj. Mohd. Noor, Norzailawati; Wan Mohamad, Wan Ramlah (IIUM Press, 2017)
Open space provides many functions in urban context that benefits people`s quality of life. Planning an effective open space for the community is essential to ensure it can run its function very well. Malaysia as a developing country has experienced a drastic growth with many lands has to be developed. This phenomenon disturbed the open space planning in an area in terms of the equality of open space distribution, open space’s role in providing a platform for community to socialize and open space’s characteristics to meet the users demand. This book focuses on good planning of open space components in assessing its function as a social place for the community in a neighborhood area with the integration of geospatial method of GIS and Remote Sensing. The idea for the book began to take shape when we saw many neglected and problematic open spaces appeared. The study on this open space has been distributed into six main chapters bringing an understanding of methodologies in extracting a function. Chapter one discusses on the introduction and outlined the goal and aims of this book. Chapter two elaborates on the critical literatures that relates to fundamental of open space in urban planning and also outlined the use of geospatial applications in attending a subject matters. Chapter three typically discusses about detailed methodology that has been used in this book. Further analysis and findings have been in chapter four, analyzing an effectiveness of open space planning with the integration of GIS and remote sensing applications, while the full result is explained in chapter five and conclusion of this book in chapter six. With this book, we also hope to remind those who have forgotten on how valuable the land is, as one of important natural resources on earth. An effective planning of open space will not only benefit to human living, but also towards the environment. Finally, we would like to thank all those who participated in producing this book especially the Department of Urban and Regional Planning in Kuliyyah of Architecture and Environmental Design and also the International Islamic University Malaysia.